Mecanismo de catálise e dinâmica protéica da enzima salicilato hidroxilase - Stefanya Velasquez Gomez (2015)
The goal of this study was to characterize the enzyme salicylate hydroxylase (NaHG) of Pseudomonas putida strain G7 regarding its protein dynamics and mechanism of catalysis. This enzyme is aflavine-dependent monooxygenase participating in the naphthalene degradation pathway at cost of NADH and O2 catalyzing the oxidative decarboxylation of salicylic acid (SA) to yield catechol. The analysis of the structural data obtained by small angle X-ray scattering (SAXS) showed that NahG unbound to FAD has undergone a structural contraction relative to the holoenzyme. Likewise, fluorimetric titration revealed that FAD binding was followed by strong suppression of the fluorescence at 340nm and increased of the quantum yield at 524 nm, suggesting that tryptophan residues underwent a change in their environment and near to FAD produced fluorescence resonance energy transfer (FRET). The Km values for FAD and O2 are within the order of enzyme concentration used in the experiment as determinated by kinetic parameters for NahG, indicating that the reaction between O2 and FAD to form the C4a-hydroperoxiflavine complex was highly favorable. These results suggested that the rate-determining step occur after any event of C4a-hydroperoxiflavine formation. The kinetic data as a function of pH for the native and mutants (H110N and H322Y)NahG indicatedthe participation of two isoforms in the catalysis of the oxidative decarboxylation reaction of salicylic acid. The deprotonation or mutation of these histidine residues promoted catalysis, whereas decreased the affinity of NahG by AS. The Log kcat-pH profiles showed three ionization constants, two of these constants were attributed to H110 and the peroxyl group of C4a-hydroperoxiflavine. Kinetic studies for substituted salicylic acids showed a curved Hammett profile for log kcat. This indicated change of the rate-determining step of the reaction, which occurs by an electrophilic aromatic substitution (SEAr)type mechanism.